Beauty Advertisement Products in Forming the Reality of Society: A Critical Discourse Analysis - Didin Nuruddin Hidayat; Desruinova Kusuma; Alek Alek; Rahmah Purwahida; Maya Defianty (Universitas Hamzanwadi, 2020)
Through advertisements aired on television, electronic media, online, and printed media, it is easy for the public to obtain product information from various brands displaying attractive images, visuals, and texts. Indeed the most significant influence in advertising is the use of text that can change the perceptions and perspectives of potential consumer communities. The study aims to analyze the advertisement of beauty products of two competing brands in gaining sympathy from the public potential customers. Despite the fact that some research studies have attempted to reveal the ideology of the beauty advertisements from a critical discourse analysis perspective, little has been done to uncover the comparative studies on local and international beauty products. To obtain the data, this study examined the advertisements of two competing beauty products that have been displayed on online media (YouTube). These advertisements were analyzed by using Critical Analysis (CDA) by Norman Fairclough. CDA was divided into three interrelated dimensions: texts, discourse practices and socio-cultural practices. The findings revealed that the texts in the advertisements were formulated in such a way for the purpose of persuading and attracting the sympathy of potential buyers. In addition, the texts were also created by elevating existing realities and shaping certain realities in society so that the advertisements achieved the ultimate goal of reaching the sympathy of the potential buyers.